AN ANALYSIS OF STUDENTS’ NEEDS OF ENGLISH FOR ENGINEERING AT TENTH GRADE STUDENT OFSMK N 1 BETARA ACADEMIC YEAR 2017/2018 - Arya Andana; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2019)
This research is to analyze the learner’s needs of English for Specific Purpose (ESP) at SMK N 1 Betara especially in engineering program because English is important for students. In English for Specific Purpose (ESP), English is taught to meet the English needs in area of specialization. The needs in area of specialization are worth considering since the language we speak and write varies from one context to another. The purpose of this researcher wants to examine the learner’s needs of English for Specific Purpose (ESP). This research applied a mixed-method. The combination of both quantitative and qualitative research targeted students of SMK N 1 Betara in engineering program especially in tenth grade with 31 participants. The result of this research in students’ English language course preferences 41,9 % want to learn English accordance with the material they need in engineering. In students’ results regarding the language aspects of the English language course, more than half of students (61,3 %) want to learn English more specific, it means they wanted English lesson associated with their department of engineering that can be useful as in the job.